(untitled) (Al-Academy, 2016)
The woman’s choice of clothing is no longer supported on the basis of the available forms of design in general. It is the interaction of design relationships with the receiver structure that reflects the character of integrated women with an emphasis on attractions pulling attention, all of these interventions reach us to the need to emphasize through this search Picking the perfect symbols of heritage in every sense of the popular beliefs of the employed in the designs of apparel fabrics women’s home included a search of four chapters deal with the first problem of the research which you can employ the traditional symbols and popular beliefs in the designs of household apparel fabrics in order to raise the aesthetic value and utility of functional?The most important goals is to provide design proposals for the employment of traditional symbols and popular beliefs in the designs apparel fabrics Women’s home and the limits of research and determine the terms -alrmoz - heritage - popular beliefs -desin fabrics. And ensure that Chapter II the first two sections metaphor of traditional symbols and folk beliefs and second designs apparel fabrics Women’s home the third quarter included the research methodology and the proposed designs, of which there were seven designs, The fourth chapter has included the conclusions and the most important was that the alignment of the traditional symbols of designs household clothing appeared as a result of their distribution in a manner commensurate with the final functional aspect in terms of distribution within the basic unit one and repeating one of the methods of repetition that keeps the continuity of their appearance on canvas clothed women . It is space, and the recommendations and then The sources abstract in English